The Effect of Work-Life Balance, Internal Communication, And Workload on Employees Turnover Intention - Maulina, Amanda; Mayesti, Afrilia; Hardjowikarto, Dharliana Ayu; Sunimah, Sunimah (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: The aim of this study is to investigate the relationship between turnover intention and workload, work-life balance, and internal communication. One significant element influencing a company's personnel stability is turnover intention, so understanding the factors that contribute to employee intention to leave is crucial in efforts to retain employees. Design/methodology/approach: Using a quantitative method with a causal approach, this study involved 129 respondents consisting of permanent employees of the company. With the use of SPSS software version 25, data was gathered via questionnaires and subjected to linear regression analysis. Findings: With a regression coefficient of -0.278 and a significance value of 0.001, the findings demonstrated that work-life balance significantly and negatively affects turnover intention. Turnover intention is similarly negatively impacted by internal communication, with a regression coefficient of -0.359 and a significance level of 0.002. On the other hand, where the regression coefficient is 0.360 and the significance is 0.001, workload positively affects turnover intention. Turnover intention is significantly impacted by all three independent variables at the same time. This model can account for 27.4% of the variation in turnover intention, according to its F value of 15.708 and R Square of 0.274. These findings indicate that companies can reduce turnover intention by improving work-life balance, improving internal communication, and controlling workload effectively. By implementing these strategies, companies can reduce employees' intention to leave the company. Paper type: Research paper.